Imitation, opposition and innovation of social forms: Finitude and infinitude in Gabriel Tarde’s Social Laws Imitación, oposición e innovación de las formas sociales: Finitud e infinitud en Las Leyes Sociales de Gabriel Tarde - Tomás Sánchez-Criado (Athenea Digital, 2011)
<!--[if gte mso 9]> 120 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <style>
/* Style Definitions */
table.MsoNormalTable
{mso-style-name:"Tabla normal";
mso-tstyle-rowband-size:0;
mso-tstyle-colband-size:0;
mso-style-noshow:yes;
mso-style-priority:99;
mso-style-parent:"";
mso-padding-alt:0cm 5.4pt 0cm 5.4pt;
mso-para-margin:0cm;
mso-para-margin-bottom:.0001pt;
mso-pagination:widow-orphan;
font-size:10.0pt;
font-family:"Times New Roman","serif";}
</style> <![endif]--> In this text I present a selection of fragments of the book ‘The social laws' by Gabriel Tarde (1843-1904), published originally in 1898 and translated into Spanish at the beginning of the 20th century. After a long time condemned to oblivion Gabriel Tarde has been reinvigorated in recent decades for the pantheon of social sciences, even reaching the point of becoming a very relevant author for Actor-Network Theory (no less than Bruno Latour has turned him into ‘ANT's ancestor'). However, I believe that the recuperation of Tarde's works could lead us to far more interesting discussions than a new mythic of ancestral figures. In this introduction I press for a more direct approach to Tarde's writings, something which might allow us to go beyond any presentist use of a historical figure to prop up a ready-made theory for mass-consumption. For this reason, I would like to propose to focus on Tarde's very own descriptions of the ‘laws' of social life, made out of -potentially infinitesimal- social forms which repeat and differentiate -something he refers as the processes of imitation, opposition and innovation-. In that vein, I would like to mention some contemporary critical appraisals of those formulations in terms of ‘laws' or Tarde's treatments of the scale of the social -where special attention is put on the relation he establishes between the finitude and infinitude of social forms-. En este texto presento una selección de fragmentos del libro “Las leyes sociales” de Gabriel Tarde (1843-1904), publicado originalmente en 1898, y traducido en castellano a principios del siglo XX. Después de un largo olvido Tarde ha sido revigorizado para el panteón de las ciencias sociales, llegando a ser convertido en un autor muy relevante para la teoría del actor-red (incluso siendo mencionado por Bruno Latour como su antepasado). Pero creo que la recuperación a la que ha sido sometida la obra de Tarde puede llevarnos a discusiones más interesantes que las de una nueva mítica de las figuras ancestrales. En esta introducción abogo más bien por una aproximación directa a la propia obra de Tarde, lo que nos permitiría ir más allá de cualquier uso presentista de una figura histórica para apuntalar una teoría precocinada para el consumo de masas. Es por esto que propongo nos centremos críticamente en los propios argumentos de Tarde, que describe “las leyes” de la vida social, hecha de formas potencialmente infinitesimales que se repiten y se diferencian (a lo que él se refiere como procesos de imitación, oposición e innovación). Y mencionaré a tal efecto algunas consideraciones críticas contemporáneas que ha recibido esta formulación en términos de leyes o su tratamiento sobre la escala de lo social, haciendo especial hincapié en la relación que establece entre la finitud y la infinitud de las formas sociales.